Polymeric Ionic Liquid Immobilized onto Paper as Sorptive Phase in Microextraction - Toledo-Neira, C; Toledo-Neira, C (Elsevier B.V., 2020)
A new planar sorptive phase based on the simple immobilization of polymeric ionic liquids on paper is proposed. The sorptive phase can develop hydrophobic or mixed-mode (combining hydrophobic and ion exchange) interactions with the target analytes. The polymer is prepared by the Radziszewski reaction, which takes place in aqueous media, and it has been thoroughly characterized by different techniques including infrared spectroscopy, matrix-assisted laser desorption/ionization coupled to high-resolution mass spectrometry and proton nuclear magnetic resonance. Three different strategies aimed to immobilize the polymeric ionic liquid on paper have been evaluated. Among them, simple thermal curing at 120 °C was selected. The as-prepared paper has been evaluated for the extraction of several non-steroidal anti-inflammatory drugs from urine, the analytes being finally determined by liquid chromatography with tandem mass spectrometry. The method detection limits were 3.8, 7.2, 6.8, 9.4, 15.7, and 5.1 μg/L for indomethacin, diclofenac, tolmetin, ketoprofen, naproxen, and ibuprofen, respectively. Calibration models were linear (R2 > 0.9949) up to 1000 μg/L. The intra-day precision, expressed as relative standard deviation and calculated at three different concentrations levels (limit of quantification, 250 μg/L, and 1000 μg/L), varied between 1.1 and 13%. The accuracy, calculated as relative recovery, was in the range from 72 to 95%, thus being considered appropriate. The easiness of polymeric ionic liquid paper synthesis and the multi-sample extraction protocol designed allows the processing of a high number of samples at the same time. © 2019 Elsevier B.V.